Talking Trade: Language Barriers in Intra-Canadian Commerce - Nicolas Sauter (FIW - Research Centre International Economics, 2009)
This paper tests for one mechanism that can explain the existence of a language barrier to trade. Specifically, I ask if those industries that require more cross-border communication in order to export their products trade more between Canadian provinces that know the other's language(s). I find that trade in industries with a need to communicate directly (orally) with importers increases with the probability that people in another province speak the same language. This finding can fill a missing link in the empirical trade literature, which lacked convincing arguments for the observed correlation between language commonality and the total volume of trade.
Keywords: F10; F15; F40; 330; Language; Trade cost; Gravity model; Canada